2017
DOI: 10.1371/journal.pone.0179431
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the receptor pharmacology, pharmacokinetics, and pharmacodynamics of NKTR-214, a kinetically-controlled interleukin-2 (IL2) receptor agonist for cancer immunotherapy

Abstract: Cytokines are potent immune modulating agents but are not ideal medicines in their natural form due to their short half-life and pleiotropic systemic effects. NKTR-214 is a clinical-stage biologic that comprises interleukin-2 (IL2) protein bound by multiple releasable polyethylene glycol (PEG) chains. In this highly PEG-bound form, the IL2 is inactive; therefore, NKTR-214 is a biologic prodrug. When administered in vivo, the PEG chains slowly release, creating a cascade of increasingly active IL2 protein conju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
118
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(118 citation statements)
references
References 36 publications
(54 reference statements)
0
118
0
Order By: Relevance
“…It currently is in clinical development as both a monotherapy and in combination with anti-PD-1 antibodies. 30 The current study data may support a future combination strategy of NKTR-214 or ALKS-4230 and VEGF inhibition in the second-line or subsequent treatment setting in patients with advanced melanoma as an outpatient and potentially less toxic regimen.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…It currently is in clinical development as both a monotherapy and in combination with anti-PD-1 antibodies. 30 The current study data may support a future combination strategy of NKTR-214 or ALKS-4230 and VEGF inhibition in the second-line or subsequent treatment setting in patients with advanced melanoma as an outpatient and potentially less toxic regimen.…”
Section: Discussionmentioning
confidence: 62%
“…NKTR-214 consists of the IL2 protein bound by multiple slowly releasable polyethylene glycol chains, acting as a kinetically-controlled IL2 receptor agonist with evidence that it favors activation of CD8+ T cells over regulatory T cells. It is currently in clinical development as both a monotherapy and in combination with anti-PD-1 antibodies 30 . Our data may support a future combination strategy of NKTR-214 or ALKS 4230 and VEGF inhibition in the second or subsequent line treatment setting in advanced melanoma as an outpatient and potentially less toxic regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NKTR-214 36 ), these findings are encouraging and could lead to future integration with wearable or implanted lightdelivery devices [37][38][39][40][41] which modulate drug activation. Consistent with other PEGylated cytokines, 36 we found that bioinspired, polymer-induced latency was able to prolong scIL-12 plasma circulation approximately 16-fold, potentially precluding the need for frequent, high dosing and improving tissue drug exposure in treatment settings.…”
Section: P R E P R I N T C O P Ymentioning
confidence: 91%
“…Polydimethylsiloxane (PDMS) tissue phantoms were prepared as described previously. [56][57][58] Briefly, Sylgard 184 elastomer and curing agent (Dow Corning) was doped with titanium dioxide (0.3-1.0 µm rutile, Atlantic Equipment Engineers) and india ink (Higgins 44201) to concentrations which approximate attenuated light transmission through human tissue (36,20, and 42% transmission of 365 nm light through epidermis, dermis, and 2 mm hypodermis tissue, respectively). 59 Solutions were degassed and sequentially cast into rectangular silicone molds prior to measurement of LED light transmission using a thermal power sensor (ThorLabs).…”
Section: P R E P R I N T C O P Ymentioning
confidence: 99%